The Effect of Sales Growth and Leverage on Tax Avoindance with Institutional Ownership as a Moderating Variable in Pharmaceutical Sub-Sector Companies on the Indonesia Stock Exchange - Ria Anggita Zen. M; Widia Astuty; Syarfrida Hani (Universitas Islam Sumatera Utara, 2023)
This study aims to determine the effect of sales growth and leverage on tax avoidance with institutional ownership as a moderating variable in pharmaceutical sub-sector..companies.. listed..on..the..Indonesian..stock..exchange. ..This..study uses statistical analysis methods that are used to explain the descriptive data of the overall variables. The number of samples analyzed was 50 samples of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. sample using purposive sampling technique. Analysis of research data using multiple linear regression test and Moderated Regression Analysis (MRA). The results of this study indicate that sales growth has an effect on tax avoidance, meaning that if sales growth the level will also increase. Leverage affects tax avoidance, which means that if the level of debt is high, the level of tax avoidance will also increase. Institutional ownership is able to weaken sales growth towards tax avoidance, the higher the level of institutional ownership in the company will increase supervision of the company. And institutional ownership is able to weaken leverage against tax avoidance, with high institutional ownership, institutions are very concerned about the level of debt used by the company to meet the company's operational activities.